2001
DOI: 10.1152/ajpcell.2001.280.4.c836
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of a liver isoform of the small conductance Ca2+-activated K+ channel SK3

Abstract: Small conductance Ca2+-activated K+ (SK) channels have been cloned from mammalian brain, but little is known about the molecular characteristics of SK channels in nonexcitable tissues. Here, we report the isolation from rat liver of an isoform of SK3. The sequence of the rat liver isoform differs from rat brain SK3 in five amino acid residues in the NH3 terminus, where it more closely resembles human brain SK3. SK3 immunoreactivity was detectable in hepatocytes in rat liver and in HTC rat hepatoma cells. Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
39
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 28 publications
8
39
0
Order By: Relevance
“…Coverslips were washed three times with TBS and then mounted on slides with Aqua Polymount (Polysciences). Prepared slides were analyzed on a Bio-Rad MRC 1024 ES laser scanning confocal microscope as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
“…Coverslips were washed three times with TBS and then mounted on slides with Aqua Polymount (Polysciences). Prepared slides were analyzed on a Bio-Rad MRC 1024 ES laser scanning confocal microscope as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
“…Opening in response to an increase in cytosolic [Ca 2ϩ ] i in the 200 -500 nM range (2), SK Ca channels modulate the firing pattern of neurons by generating slow membrane after hyperpolarizations (3)(4)(5). In the liver, they are believed to play a role in metabolic stress responses (6), and in human Jurkat T cells, they promote calcium entry in response to a mitogenic stimulus (7). SK Ca channels have also been implicated in fasciculations in denervated skeletal muscle (8) and in myotonic dystrophy (9).…”
Section: Camentioning
confidence: 99%
“…Small conductance Ca 2ϩ -activated K ϩ channels (SK Ca ) 1 tightly couple calcium signaling and regulation of membrane excitability in excitable cells and influence membrane potential in non-excitable cells (1)(2)(3)(4)(5)(6). Three closely related genes, SK1, SK2, and SK3, known also as K Ca 3.1-3.3, KCNN1-KCNN3, and SKCa1-SKCa3, encode SK Ca proteins (7)(8)(9).…”
mentioning
confidence: 99%
“…Expression of SK3 has been reported in the brain, skeletal muscle, endothelium, uterus, and hepatobiliary cells (6,7,(13)(14)(15). Recent quantitative RT-PCR studies have identified SK3 transcripts in other human tissues including the trachea, thyroid, spleen, and thymus (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation